Enhancing Success of Stunting Eradication: Risk Factor Identification and Booklet-Based Intervention in Stunting Communities - Gharini Sumbaga Narhadina; Devita Diatri; Rifka Widianingrum; Umniatuz Zahroh (Jurnal Empathy Pengabdian Kepada Masyarakat, 2025)
Background: Stunting is a form of chronic malnutrition that affects growth and development during early life. Stunting remains a government priority, with a target to reduce its prevalence to 14%, yet it continues to rank high in the Lamper Tengah Sub-district. This situation is attributed to the lack of family knowledge regarding the risks and long-term impacts of stunting. Therefore, this program aimed to implement stunting risk screening and a booklet-based intervention entitled “Control of Stunting Risk Factors” within the Stunting Community in Lamper Tengah Sub-district, Semarang City. Methods: This community service activity was carried out in Lamper Tengah Village, targeting 10 families with stunted children. The activity methods included preparation, anthropometric measurements, filling out questionnaires on stunting risk factors, and distributing and presenting the booklet “Stunting Risk Factors.” The evaluation stage was carried out by assessing the mothers' level of knowledge about stunting before and after the intervention. Results: Among stunted toddlers, 60% are female, 60% do not receive exclusive breastfeeding, and only 20% practice responsive feeding. After the intervention, the proportion of families with good knowledge levels increased from 80% before the activity to 100% after the activity. Conclusion: The results of the activities show that this community service program is able to increase mothers' knowledge about the risk factors for stunting. Therefore, similar activities need to be continued and expanded to include more participants, accompanied by in-depth counseling and practical guidance on active feeding practices before pregnancy, during pregnancy, and after childbirth to support efforts to reduce stunting rates in Semarang City.